Tungstophosphoric Acid-Catalyzed Synthesis of Pyrazolones in Water - Min, Zhen-Li; Hu, Xia-Min (Asian Journal of Chemistry, 2013)
A convenient and efficient method for the synthesis of pyrazolones via condensation of hydrazine derivatives with b-keto esters in water catalyzed by tungstophosphoric acid is described. It eliminates the need to dry solvents and substrates before use and the products are easily isolated with high yields.